2015
DOI: 10.1021/acs.chemmater.5b03444
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasmall Cu3N Nanoparticles: Surfactant-Free Solution-Phase Synthesis, Nitridation Mechanism, and Application for Lithium Storage

Abstract: New chemical pathways are of fundamental interest for materials synthesis. Here, we report a novel surfactant-free, solution-phase, low-temperature route to crystalline, ultrasmall (∼2 nm) Cu 3 N nanoparticles via a one-step reaction between copper(II) methoxide and benzylamine. We propose a reaction mechanism for Cu 3 N formation based on the gas chromatography− mass spectrometry (GC−MS) analysis of the organic reaction byproducts. The reaction pathway involves reduction of the Cu(II) to Cu(I) by benzylamine,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 47 publications
4
44
0
Order By: Relevance
“…The Coulombic efficiency can be improved to above 97.4% with a current density up to 1 mA cm −2 in corrosive carbonate electrolyte on copper (Cu) current collector and if applied on porous Li-coated polyimidezinc oxide electrode (Li-coated PI-ZnO), the coating rendered a 40% increase in cycle life when paired with Li titanate (LTO). [30,31] Fortunately, the electrochemical potential of the Li metal anode will usually not exceed the decomposition voltage (≈0.5 V theoretically) of Li 3 N under normal operation conditions, [32] which guarantees the validity of our proposed coating as a Li-ion conducting artificial SEI on Li metal electrode. Cu 3 N nanoparticles with a size of sub-100 nm were synthesized via a facile one-step reaction between Cu(II) methoxide (Cu(OMe) 2 ) and benzylamine ( Figure S1, Supporting Information).…”
Section: Doi: 101002/adma201605531mentioning
confidence: 53%
See 1 more Smart Citation
“…The Coulombic efficiency can be improved to above 97.4% with a current density up to 1 mA cm −2 in corrosive carbonate electrolyte on copper (Cu) current collector and if applied on porous Li-coated polyimidezinc oxide electrode (Li-coated PI-ZnO), the coating rendered a 40% increase in cycle life when paired with Li titanate (LTO). [30,31] Fortunately, the electrochemical potential of the Li metal anode will usually not exceed the decomposition voltage (≈0.5 V theoretically) of Li 3 N under normal operation conditions, [32] which guarantees the validity of our proposed coating as a Li-ion conducting artificial SEI on Li metal electrode. Cu 3 N nanoparticles with a size of sub-100 nm were synthesized via a facile one-step reaction between Cu(II) methoxide (Cu(OMe) 2 ) and benzylamine ( Figure S1, Supporting Information).…”
Section: Doi: 101002/adma201605531mentioning
confidence: 53%
“…[11][12][13] For the first time, the approach minimized the volumetric change at the whole electrode level during Li plating/stripping. [30] The resulting nanoparticles can be readily dispersed in tetrahydrofuran (THF) with SBR to form a stable colloidal solution, which can then be applied on the Li surface via doctor blade casting or drop casting to afford a conformal protection layer. Other an ideal SEI.…”
Section: Doi: 101002/adma201605531mentioning
confidence: 99%
“…Accordingly, one could assume that benzylamine might be able to act as nitrogen donor for the formation of metal nitrides. Unfortunately, most of the reactions in benzylamine still result in metal oxide nanoparticles with the only exception being copper nitride …”
Section: Chemical Formation Mechanismsmentioning
confidence: 99%
“…In contrast to titanium isopropoxide, the reaction between the copper alkoxide Cu(OCH 3 ) 2 and benzylamine indeed led to the formation of copper nitride rather than copper oxide . GC‐MS data indicated that initially a benzylamine molecule reacted with two Cu(OCH 3 ) 2 to yield methanol, CuOCH 3 and benzenemethanimine (Scheme , Equation (1)).…”
Section: Chemical Formation Mechanismsmentioning
confidence: 99%
“…Among the organic solvents used in surfactant-free nonaqueous methods, benzyl alcohol and its derivatives, first reported by Niederberger et al ., are the most brilliant2526. Through the versatile solvents, numerous semiconductors including nitrides2728, sulfides29, binary and ternary oxides3031 have been effectively synthesized. It covers most of the semiconductors used in heterogeneous photocatalysis.…”
mentioning
confidence: 99%